2002
DOI: 10.1029/2001jc000838
|View full text |Cite
|
Sign up to set email alerts
|

Two‐layer tidal modeling of the Yellow and East China Seas with application to seasonal variability of the M2 tide

Abstract: [1] The baroclinic response of tide and tidal currents in the Yellow and East China Seas is investigated using a two-layer numerical model. Seasonal variability in the M 2 tide, especially the smaller summer amplitudes prevailing along the Korea/Tsushima Strait [Kang et al., 1995], is investigated by a series of numerical experiments with varying degrees of stratification specific to winter and summer. Model results show that the summer amplitudes of the M 2 tide around the southwestern tip of the Korean penin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
49
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 25 publications
10
49
0
Order By: Relevance
“…However, tidal analyses have suggested that the TM1 and KPG2 data could be used to study temporal variations of tidal constituents in excess of 1 hPa, even though they are a little noisier than the Paros data. The tidal constituents are known to change seasonally (e.g., Kang et al, 2002), interannually (e.g., Munk et al, 1965), and secularly (e.g., Ray, 2006, and references therein) although their mechanisms are still poorly understood. Even the theoretically expected 18.6-year nodal modulation has recently been paid attention in relation to bi-decadal climate changes (e.g., Osafune and Yasuda, 2006;Ray, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, tidal analyses have suggested that the TM1 and KPG2 data could be used to study temporal variations of tidal constituents in excess of 1 hPa, even though they are a little noisier than the Paros data. The tidal constituents are known to change seasonally (e.g., Kang et al, 2002), interannually (e.g., Munk et al, 1965), and secularly (e.g., Ray, 2006, and references therein) although their mechanisms are still poorly understood. Even the theoretically expected 18.6-year nodal modulation has recently been paid attention in relation to bi-decadal climate changes (e.g., Osafune and Yasuda, 2006;Ray, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal variations of ocean tides have been reported in terms of sea level by a number of studies (e.g., Tamura, 1985;Pugh, 1987;Kang et al, 1995Kang et al, , 2002Leeuwenburgh et al, 1999;Blanton et al, 2004) and, in spite of limited studies, in terms of OBP (e.g., Tamura et al, 1986;Blanton et al, 2004). Tamura et al (1986) used the OBTM data of JMA (Isozaki et al, 1980) and pointed to a seasonal variation of the M 2 constituent, without detailed discussions.…”
Section: Tidal Frequency Bands-evaluating Seasonal Variations Of Tidamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the fact that tidal constants vary seasonally has been known for many years but the reasons for such variations, which occur especially in shallow waters (e.g. Pugh and Vassie, 1992;Kang et al, 2002) and at high latitudes (e.g. Prinsenberg, 1988;Kagan and Sofina, 2009), remain poorly understood.…”
Section: Timing or Calibration Errors Or Other Data Irregularitiesmentioning
confidence: 99%
“…There have been many results about tide modeling in Chinese Sea ( Bao et al, 2001;Fang et al, 2004;Kang et al, 2002;Lefèvre et al, 2000;Song et al, 2013;Wang et al, 2014;Yao et al, 2012;Yu et al, 2003 ) . Some Chinese scientists have studied the effects of SLR on Chinese Sea ( Kuang et al, 2014;Yu et al, 2003Yu et al, , 2007 , but the conclusions were not consistent, especially the changes of tidal range and phase lags in local Bohai Sea.…”
Section: Introductionmentioning
confidence: 99%